CONGREGATIONAL PRAYER GUIDANCE TO ENHANCE THE SPIRITUALITY OF CHILDREN WHO COMMIT SEXUAL HARASSMENT AT SENTRA PARAMITA MATARAM - Jannah, Miftahul; Saleh, Hendri (Universitas Islam Negeri Mataram, 2024)
Sentra Paramita Mataram provides mental and spiritual therapy to children who have engaged in criminal behavior. This study focuses on the congregational prayer therapy program offered at Sentra Paramita Mataram, specifically for children involved in sexual offenses, with a sample of eight (8) participants. These children face various underlying issues, one of which pertains to their relationship with Allah SWT, particularly regarding their understanding and practice of obligatory prayers. Many of them struggle with comprehending the pillars and conditions for valid prayer, reciting the prayers properly, and memorizing the prayer formulas. These challenges indirectly affect their behavior, making them prone to negative actions. This research employs a qualitative approach with a case study design, utilizing observation, interviews, and collaboration for data collection. The findings indicate that consistent participation in congregational prayer therapy, conducted five times daily under the supervision and guidance of caregivers, positively influences the children’s behavior and character. This transformation becomes evident after more than one month of therapy. The prayer therapy, which is part of the court-mandated sentence for these children, plays a significant role in their behavioral improvement during their time at Sentra Paramita Mataram.